2020
DOI: 10.3390/app10041504
|View full text |Cite
|
Sign up to set email alerts
|

DERN: Deep Ensemble Learning Model for Short- and Long-Term Prediction of Baltic Dry Index

Abstract: The Baltic Dry Index (BDI) is a commonly utilized indicator of global shipping and trade activity. It influences stakeholders’ and ship-owners’ decisions respecting investments, chartering, operational plans, and export and import activities. Accurate prediction of the BDI is very challenging due to its volatility, non-stationarity, and complexity. To help stakeholders and ship-owners make sound short- and long-term maritime business decisions and avoid market risk, we performed short- and long-term prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Using the one-week-ahead NARX forecast model proposed in this work, public health managers have more time to plan and respond. Future studies will consider an extension into multi-steps-ahead forecasting, since RNNs have already been successfully applied to such cases in other domains [44], [17]. Additionally, other deep learning network architectures will be considered, such as the transformer model applied in [9] for multi-step-ahead forecasting of influenza epidemics prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Using the one-week-ahead NARX forecast model proposed in this work, public health managers have more time to plan and respond. Future studies will consider an extension into multi-steps-ahead forecasting, since RNNs have already been successfully applied to such cases in other domains [44], [17]. Additionally, other deep learning network architectures will be considered, such as the transformer model applied in [9] for multi-step-ahead forecasting of influenza epidemics prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Uyar et al [34] presented one trained recurrent fuzzy neural system with the use of a genetic algorithm for improving long-term dry cargo freight rates prediction to be more accurate. As an efficient strategy to improve the forecasting ability of a single model, ensemble learning has been widely used to improve the model performance [35][36][37][38]. For example, Kamal et al [35] developed a deep ensemble recurrent network of recurrent neural network (RNN), long-short-term memory (LSTM), and gated rectified unit neural network (GRU) to improve the BDI predictive performance, and results showed that the ensemble method outperforms the single deep-learning approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an efficient strategy to improve the forecasting ability of a single model, ensemble learning has been widely used to improve the model performance [35][36][37][38]. For example, Kamal et al [35] developed a deep ensemble recurrent network of recurrent neural network (RNN), long-short-term memory (LSTM), and gated rectified unit neural network (GRU) to improve the BDI predictive performance, and results showed that the ensemble method outperforms the single deep-learning approach. Tan et al [37] proposed an LSTM-based deep ensemble learning model that combined bagging, random subspace, and boosting to forecast ultra-short-term industrial power demand, and they found out that the proposed model obtains higher accuracy and robustness than LSTM, eXtreme Gradient Boosting (XGBoost), and other time series methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, several experiments were conducted with different LSTM variants, including a variable number of units and hidden layers as well as custom training loops for sequence forecasting. However, it is evident that, while changes in the structural parameters of an LSTM can boost model performance and achieve faster training time through faster convergence, stable and reliable results are derived from the aggregation of multiple LSTMs and the construction of ensemble models [34]. Therefore, for the purposes of this study, an LSTM ensemble was considered for the forecasting experiments and the weighted average of the ensemble members was used for each representation of the predicted output.…”
Section: Long Short-term Memory Networkmentioning
confidence: 99%